2016
DOI: 10.21873/anticanres.11088
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Maternal Embryonic Leucine Zipper Kinase (MELK) Correlates to Malignant Potentials in Hepatocellular Carcinoma

Abstract: MELK expression in HCC is extremely intense compared to its expression reported in other types of cancer. MELK could be a promising effective tumor marker of HCC and further consideration is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 19 publications
4
16
0
Order By: Relevance
“…Additionally, high MELK expression at the RNA level was associated with low OS and the difference was significant ( Figure 1C, 1D ). These results are consistent with previous reports [ 13 , 22 ]. Second, we further validated them by qRT-PCR analysis in an independent and random cohort of HCC samples consisting of 32 hepatocellular liver tissues and adjacent liver tissues ( Figure 2A ).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Additionally, high MELK expression at the RNA level was associated with low OS and the difference was significant ( Figure 1C, 1D ). These results are consistent with previous reports [ 13 , 22 ]. Second, we further validated them by qRT-PCR analysis in an independent and random cohort of HCC samples consisting of 32 hepatocellular liver tissues and adjacent liver tissues ( Figure 2A ).…”
Section: Discussionsupporting
confidence: 94%
“…Increasing evidence proves that various genes up-regulated or down-regulated in hepatocellular liver tissues can be considered as special prognostic markers and therapeutic targets [ 21 ]. Recent studies reported that MELK expression is increased in many digestive malignant tumors, such as gastric [ 12 ], hepatocellular [ 13 ], and colorectal [ 14 ] tumors. Additionally, high MELK expression indicates poor clinical outcome [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations